Some remarks on the response of pressure fields to changing surface roughness - Jost Nielinger; Rainer Roth; Thomas Prenosil (Meteorologische Zeitschrift, 1996)
When depressions move from sea- to land surfaces, the increasing roughness leads to rising friction forces and is responsible for higher values of the cross isobaric flow of air mass. Considering lows, this flow is directed to the center of the pressure system and causes the process of Ekman-pumping as well as the rise of surface pressure in the covered area. This study presents an approach to estimate the characteristic time scales of this response to changing lower boundary conditions and the afterwards adapted geostrophic windspeed in certain distances to the center. The results are compared with those of a regional weather forecast model. The scheme seems to be sufficiently accurate, and is therefore suitable as a first guess instrument.